Does Financial Literacy Drive Financial Happiness and Job Success for Muslim? Insights from Thailand’s Southern Border Provinces - Meesook, Kanokwan; Kaje, Anwa; Promma, Pimpisa; Vongchavalitkul, Busaya; Usman, Berto; Aujirapongpan, Somnuk (International Review of Management and Marketing, 2026)
This research aims to 1) investigate and explore the influence of financial literacy on financial happiness, 2) examine the influence of financial literacy on job performance, and 3) assess the impact of financial happiness on job performance among Muslim state officers in the three southern border provinces of Thailand, namely Yala, Pattani, and Narathiwat. This study employs a quantitative research approach, utilizing questionnaires for data collection. The sample group consists of 510 Muslim state officers working in local administrations within the three southern border provinces. Statistical analyses included frequency, percentage, mean, and standard deviation, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study’s findings indicate that two hypotheses were supported. Hypothesis 1, which posits that financial literacy positively influences financial happiness, showed a direct effect of 0.845. Hypothesis 3, which suggests that financial happiness positively influences job performance, demonstrated a direct effect of 0.694. However, Hypothesis 2, which proposed a positive influence of financial literacy on job performance, was rejected, with a direct effect of 0.109 and an indirect effect of 0.586. These findings can be applied in various contexts to enhance the quality of life in terms of financial literacy, financial happiness, and job performance among Muslim state officers in the southern border provinces of Thailand.